2017
DOI: 10.1038/s41598-017-01843-9
|View full text |Cite
|
Sign up to set email alerts
|

Degradation mechanisms of silver nanowire electrodes under ultraviolet irradiation and heat treatment

Abstract: We report the degradation mechanisms of the silver nanowire (Ag NW) electrodes that play a significantly important role in the stability of wearable and flexible devices. The degradation mechanisms behind the increase in the sheet resistances of Ag NW electrodes were clarified by investigating the variations in the structure and the chemical composition of the Ag NW electrodes caused by ultraviolet irradiation and thermal treatment. While the shapes of the Ag NWs were affected by melting during the thermal deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 49 publications
2
53
0
Order By: Relevance
“…In literature, it has been demonstrated that the leaf skeletons when stored in tap water show significant biodegradation within a few days 58 . In addition, Ag nanowire can be readily degradable using UV irradiation and heat treatment 59 . Ag itself is not toxic to the environment and environmental species and it has been found that the bioaccumulation of the Ag leads to biologically nonreactive compounds during biological processes 60 .…”
Section: Heating Performancementioning
confidence: 99%
“…In literature, it has been demonstrated that the leaf skeletons when stored in tap water show significant biodegradation within a few days 58 . In addition, Ag nanowire can be readily degradable using UV irradiation and heat treatment 59 . Ag itself is not toxic to the environment and environmental species and it has been found that the bioaccumulation of the Ag leads to biologically nonreactive compounds during biological processes 60 .…”
Section: Heating Performancementioning
confidence: 99%
“…Let us look at each of these factors. Regarding , the oxide film and the surfactant on the surface of the NW are dependent on each NW and, even in single particles, the gap serving as the spacer changed . Meanwhile, is attributable to the time when the silver film was manufactured and, based on the average surface roughness of the silver film and the maximum height difference, it is thought that uneven spacers appeared, in part, at the time of forming the NWoM.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding 1 , the oxide film and the surfactant on the surface of the NW are dependent on each NW and, even in single particles, the gap serving as the spacer changed. 19 Meanwhile, 2 is attributable to the time when the silver film was manufactured and, based on the average surface roughness of the silver film and the maximum height difference, it is thought that uneven spacers appeared, in part, at the time of forming the NWoM. Finally, 3 suggests that lattice defects in the atomic arrangement during NW synthesis may have changes the surface shape of the NW, thus causing the multiple resonances.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the previous section, the more conductive Ag may contribute to smaller transmission losses in the printed transmission line. However, Ag generally degrades faster [11]. Consequently, degradation of the transmission loss should be investigated.…”
Section: Degradation In Transmission Lossmentioning
confidence: 99%